2022
DOI: 10.3390/admsci12030080
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Influence of Companies’ Green Communication in College Students’ Green Purchase Behaviour: An Application of the Extended Theory of Planned Behaviour Model

Abstract: In recent years, there has been a growing concern about the environmental impacts of consumers’ behaviour. As this environmental awareness increases, consumers tend to focus more on green products and how purchasing these products represents an effective way to protect the environment. Through the application of the theory of planned behaviour (TPB), in this research, we studied the influence of some key variables on college students’ green purchasing behaviour, namely perceived behavioural control, subjective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
20
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 89 publications
7
20
1
1
Order By: Relevance
“…This result shows that the presence of barriers slows the intention to purchase organic products (Liobikiene and Bernatoniene, 2017;Yadav and Pathak, 2017;Ricci et al, 2018;Carri on et al, 2023). In addition, the study supports the idea that PBC is a determining factor that encourages or restricts PI for products with ecological characteristics (Liobikiene and Bernatoniene, 2017;Yadav and Pathak, 2017;Ricci et al, 2018;Sousa et al, 2022).…”
Section: Discussionsupporting
confidence: 74%
“…This result shows that the presence of barriers slows the intention to purchase organic products (Liobikiene and Bernatoniene, 2017;Yadav and Pathak, 2017;Ricci et al, 2018;Carri on et al, 2023). In addition, the study supports the idea that PBC is a determining factor that encourages or restricts PI for products with ecological characteristics (Liobikiene and Bernatoniene, 2017;Yadav and Pathak, 2017;Ricci et al, 2018;Sousa et al, 2022).…”
Section: Discussionsupporting
confidence: 74%
“…Many scholars found a non-significant interaction between SN and intention in the TPB model (La Barbera and Ajzen, 2020). This finding is similar to the conclusions of Vermeir and Verbeke (2008), Jamil and Mat (2011), Kumar (2012), Kothe and Mullan (2015), Shin and Hancer (2016), Chen and Hung (2016), Earle et al (2020) and Sousa et al (2022). This may be because the collective self depends on social links to others gained from shared and metaphorical affinity with a particular group (Sedikides, 1993).…”
Section: Methodssupporting
confidence: 88%
“…Consumer preference and overall evaluation of a product will be greatly influenced by their attitude towards the product. Past research showed that attitude is significantly associated to PI (Abbasi et al, 2021;Qi and Ploeger, 2021;Dionysis et al, 2022;Lim et al, 2022;Sousa et al, 2022;Roh et al, 2022). Specific to the context of SE, the study by Lee et al (2021) on consumer PI on Malaysian SE products revealed a positive correlation between attitude and PI.…”
Section: Attitudementioning
confidence: 90%
See 1 more Smart Citation
“…The reviewed papers that addressed this topic also highlighted that a company’s perceived green image is built around several concepts such as eco-certification origin [ 43 ], brand image [ 40 , 48 ], brand love [ 48 ], brand loyalty [ 48 ], brand trust [ 66 ], green brand associations [ 5 ], green brand attitude [ 5 ], green brand knowledge [ 66 ], green communication [ 39 ], social media [ 42 ], and product innovation and segmentation [ 50 ].…”
Section: Resultsmentioning
confidence: 99%